Common Currency in the European System: Politological Analysis (Economic and Political Thought, 2010)
The article describes selected economic phenomena of the European system,i.e. a structure of national and European Union institutions in Europe.It mainly analyses the conditions for the system of a common currency. It presentsthe most important institutional loopholes which lower the effectivenessof managing the economy. Moreover, they result in democratic deficit bothin the European Union and in the Member states what additionally weakensthe effectiveness of management.